Clinical features of multiple sclerosis in a genetically homogeneous tropical population (2001)
Individuals affected with multiple sclerosis (MS) from a genetically homogeneous Caucasian population in Antioquia, a tropical region of Colombia, were evaluated in order to observe the clinical behavior of the disease. The frequency of clinical manifestations in 65 patients with definite MS from Antioquia was compared with those reported from temperate regions. The most common manifestations were optic neuritis and motor symptoms with absence of cerebellar symptoms. This presentation is significantly different from the frequency distribution at onset in series from temperate regions. These differences suggest that environmental factors could modify the clinical expression of MS in this population.